Achieving Sustainable Energy Security in Indonesia Through Substitution of Liquefied Petroleum Gas with Dimethyl Ether as Household Fuel - Lim, Natasya; Felixius, Vincent; Weslie, Timotius (Indonesian Journal of Energy, 2021)
Indonesia has been facing an energy security issue regarding Liquefied Petroleum Gas (LPG) consumption. The rapid increase of LPG consumption and huge import have driven the Indonesian government to develop the alternative for LPG in the household sector. Dimethyl ether (DME) is the well-fit candidate to substitute LPG because of its properties similarities. However, discrepancies in the properties, such as combustion enthalpy and corrosivity, lead to adjustments in the application. Coal is a potential raw material to produce DME, especially in Indonesia, known as the fourth-largest coal producer globally. However, the gasification of coal into DME brings a problem in its sustainability. To compensate for the emission, co-processing of DME with biomass, especially from agricultural residue, has been discovered. Recently, carbon dioxide (CO2) captured from the gasification process has also been developed as the raw material to produce DME. The utilization of CO2 recycling into DME consists of two approaches, methanol synthesis and dehydration reactions (indirect synthesis) and direct hydrogenation of CO2 to DME (direct synthesis). The reactions are supported by the catalytic activity that strongly depends on the metal dispersion, use of dopants and the support choice. Direct synthesis can increase the efficiency of catalysts used for both methanol synthesis and dehydration. This paper intended to summarize the recent advancements in sustainable DME processing. Moreover, an analysis of DME's impact and feasibility in Indonesia was conducted based on the resources, processes, environmental and economic aspects. Keywords: coal gasification, DME, energy security, LPG, sustainable